Penerapan Model Pembelajaran Kooperatif Tipe Examples Non Examples Terhadap Kemampuan Berpikir Kritis Matematika Siswa Kelas VIII SMP Negeri 9 Padangsidimpuan TP. 2022/2023 - Elvi Rosalinda Siagian; Yuni Rhamayanti; Susi Sulastri Lubis (Program Studi Matematika Universitas Graha Nusantara Padangsidimpuan, 2023)
This The problem in this research is the low ability of students' critical thinking in mathematics. To overcome this problem, this study applied the Example Non Example learning model. The aims of this study were (1) to find out students' mathematical critical thinking skills which were taught using the Example Non-Example learning model on the subject of geometric shapes better than learning without using the Example Non-Example learning model in class VIII SMP Negeri 9 Padangsidimpuan. (2) To find out the size of students' active learning activities in learning mathematics in the experimental class and the control class. The type of research used in this research is experimental research. The population in this study were students of class VIII SMP Negeri 9 Padangsidimpuan. The research sampling technique is random sampling. The instruments used to collect data were tests of critical thinking skills in mathematics in the form of essays and observations of students' learning activities. The learning tools used in this study are lesson plans, worksheets, and test instruments. The test used is a test that has been validated and is suitable for use. Hypothesis testing used two way Anava with different number of cells, with a significance level of 0.05. The results of the analysis on the two-way Anava with unequal number of cells show: (1) Students who get the Example Non-Example learning model and the ordinary learning model get different learning outcomes in mathematics (Fa = 72.82 with Ftable = 3.97). (2) Students with high, medium, and low critical thinking skills have different learning outcomes in mathematics (Fb = 38.75 with Ftable = 3.12). (3) The results of learning mathematics between students in each learning model for each level of critical thinking skills are not different (Fab = 3.59 with Ftable = 3.12). (4) The results of observing the assessment of the ability of students' learning activities in the experimental class obtained an average of 3.04 and a percentage of 76.06% with a good grade qualification while for the control class obtained an average of 2.48 and a percentage of 62.09% with a qualifying score Enough.